Maximum power point tracking (MPPT) algorithm for photovoltaic (PV) system based on parabolic prediction method
The increased consumption of electric energy during the recent decades has prompted a search for other sources of energy. One of these sources is solar energy. Photovoltaic (PV) systems are a strategic approach to exploiting the solar energy. However, the harvesting energy of the PV module is low conversion efficiency, nonlinear characteristics and dependent on the temperature and the amount of irradiance. Maximum power point tracking (MPPT) techniques are a practical solution to maximise the output of the PV system and overcome nonlinear characteristics under all circumstances. Many MPPT algorithms have been proposed. Most MPPT algorithms suffer from oscillation where the operation points oscillate around the maximum power point. As a result, the loss of power is increased. The loss of tracking under a dynamic change in irradiance is another challenge in MPPT. In this work, a new MPPT algorithm based on the Parabolic Prediction Method is proposed to track the maximum power point. The proposed method can overcome the limitation of conventional MPPT algorithms such as steady state oscillation and loss of tracking during a dynamic change in irradiance. The working principle of this method is the calculation of the maximum power from a parabolic convex function. Subsequently, a methodical scheme is sophisticated to regulate the concavity and optimum region of the approximate parabola for guaranteeing the repetitive convergence of the proposed algorithm. To validate its superiority, the proposed method is compared with the conventional P&O method in terms of steady state and dynamic change in irradiance conditions. The algorithm is carried out on a DC-DC buck converter. The verification of the proposed method has been done using MATLAB/Simulink®. The results prove that the proposed MPPT algorithm tracks the maximum power successfully within a short time of 100 ms that is less than the conventional P&O method. Besides that, the proposed method has a faster dynamic response and removes oscillations of the operating point around the maximum power point (MPP) under steady state conditions. In a dynamic change in irradiance, the MPPT algorithm needs less than 100msec to reach the new maximum power compared to the conventional P&O algorithm that needs more than 100msec. For all case tests, the proposed algorithm has zero oscillation after reaching the maximum compared to the conventional P&O algorithm that continues in oscillation even after reaching maximum power